Dupilumab for the treatment of adolescents with atopic dermatitis. (2nd July 2020) - Senner, Sonja; Seegräber, Marlene; Frey, Surina; Kendziora, Benjamin; Eicher, Laurie; Wollenberg, Andreas
ABSTRACT: Introduction: Dupilumab is a treatment option newly licensed for adolescents with moderate to severe atopic dermatitis (AD). It reduces type 2 inflammation by blocking the shared receptor subunit for IL-4/-13. Dupilumab affects three disease mechanisms in atopic dermatitis: the skin barrier, the Th2-cell differentiation and the class switch to IgE. This report is based on a systematic literature search of the PubMed Database. Areas covered: Dupilumab showed promising results in improving AD signs, symptoms and quality of life in adolescents with moderate to severe AD. The safety profile of dupilumab in adolescents with moderate to severe AD closely resembled the known safety profile of dupilumab in adults with moderate to severe AD. Injection-site reactions and conjunctivitis were the relevant side-effects. Skin infections were less frequently observed compared to placebo. Expert commentary: Dupilumab was approved by the Food and Drug Administration in March 2019 and by the European Medicines Agency in August 2019 for the treatment of adolescents with moderate to severe atopic dermatitis whose disease is not adequately controlled with topical therapies or when those therapies are not advisable. Since it is the first licensed drug it will likely become the reference drug for adolescents with moderate to severe AD.